2022
DOI: 10.3389/fnagi.2022.858162
|View full text |Cite
|
Sign up to set email alerts
|

VAMP2 Expression and Genotype Are Possible Discriminators in Different Forms of Dementia

Abstract: Vascular alterations often overlap with neurodegeneration, resulting in mixed forms of dementia (MD) that are hard to differentiate from Alzheimer’s Disease (AD). The 26 bp intergenic polymorphism of VAMP2, a key component of SNARE complex, as well as its mRNA and protein levels are associated with neurological diseases. We evaluated ApoE4 and VAMP2 26 bp Ins/Del genotype distribution in 177 AD, 132 MD, 115 Mild Cognitive Impairment (MCI) and 250 individuals without cognitive decline (CT), as well as VAMP2 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
2
1
0
Order By: Relevance
“…Several studies indicated that abnormal expression, risk genetic variants, or dysfunction of SNARE proteins are present in various neurological diseases, possibly contributing to abnormal neurotransmission and synaptic dysfunction [ 18 ]. In line with our findings, VAMP2 expression was found to be reduced in animal models or patients' brain tissues of Parkinson [ 26 ], epilepsy [ 27 ], and dementia [ 28 ]. As proposed in vascular dementia, VAMP2 _rs1150 risk allele may have a potential role in synaptic decline and vascular alterations [ 28 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Several studies indicated that abnormal expression, risk genetic variants, or dysfunction of SNARE proteins are present in various neurological diseases, possibly contributing to abnormal neurotransmission and synaptic dysfunction [ 18 ]. In line with our findings, VAMP2 expression was found to be reduced in animal models or patients' brain tissues of Parkinson [ 26 ], epilepsy [ 27 ], and dementia [ 28 ]. As proposed in vascular dementia, VAMP2 _rs1150 risk allele may have a potential role in synaptic decline and vascular alterations [ 28 ].…”
Section: Discussionsupporting
confidence: 88%
“…In line with our findings, VAMP2 expression was found to be reduced in animal models or patients' brain tissues of Parkinson [ 26 ], epilepsy [ 27 ], and dementia [ 28 ]. As proposed in vascular dementia, VAMP2 _rs1150 risk allele may have a potential role in synaptic decline and vascular alterations [ 28 ]. In these same studies, SNAP25 and STX1A expression was decreased, in opposition to our results of the SNAP25 _rs2327264 risk allele.…”
Section: Discussionsupporting
confidence: 88%
“…VAMP2 is encoded by the VAMP2 gene, which is located on chromosome 17p13.1 and consists of six exons [Costa et al, 2022]. Previous in vitro studies have demonstrated that pathogenic variants affecting its SNARE motif (sequence of the protein with a tendency to form coiled coils [Rizo and Rosenmund, 2008]) can interfere with liposomal fusion and promotion of plasma membrane "zippering" via Munc18 [Hernandez et al, 2012;Shen et al, 2015].…”
Section: Introductionmentioning
confidence: 99%